High Performance Computing on Vector Systems 2011 - Resch, Michael; Wang, Xin.; Bez, Wolfgang; Focht, Erich; Kobayashi, Hiroaki; Roller, Sabine; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The book presents the state of the art in high performance computing and simulation on modern supercomputer architectures. It covers trends in hardware and software development in general and specifically the future of vector-based systems and heterogeneous architectures. The application contributions cover computational fluid dynamics, material science, medical applications and climate research. Innovative fields like coupled multi-physics or multi-scale simulations are presented. All papers were chosen from presentations given at the 13th Teraflop Workshop held in October 2010 at Tohoku University, Japan.
Keywords: Mathematics; Chemistry; Computer science; Engineering mathematics; Mathematics; Computational Science and Engineering; Theoretical, Mathematical and Computational Physics; Appl.Mathematics/Computational Methods of Engineering; Theoretical and Computational Chemistry